Deregulation of Lipid Metabolism: The Critical Factors in Ovarian Cancer - Ji, Zhaodong; Shen, Yan; Feng, Xu; Kong, Yue; Shao, Yang; Meng, Jiao; Zhang, Xiaofei; Yang, Gong (Frontiers in Oncology, 2020)
Ovarian cancer is one of the most malignant gynecological cancers around the world. In spite of multiple treatment options, the five-year survival rate is still very low. Several metabolism alterations are described as a hallmark in cancers, but alterations of lipid metabolism in ovarian cancer has been paid less attention. To explore new markers/targets for accurate diagnosis, prognosis, and therapeutic treatments based on metabolic enzyme inhibitors, here, e reviewed available literature and summarized several key metabolic enzymes in lipid metabolism of ovarian cancer. In this review, the rate limiting enzymes associated with fatty acid synthesis ( FASN, ACC, ACLY, SCD ), the lipid degradation related enzymes ( MAGL, CPT, 5-LO, COX2 ), and the receptors related to lipid uptake ( FABP4, CD36, LDLR ), which promote the development of ovarian cancer, were analyzed and evaluated. We also focused on the review of application of current metabolic enzyme inhibitors for the treatment of ovarian cancer through which the potential therapeutic agents may be developed for ovarian cancer therapy. Keywords: ovarian cancer; lipid metabolism; potential target